(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Uterine prolapse is a type of pelvic organ prolapse where the supporting pelvic structures of uterus weakens and result in descent of uterus from its normal position. Among them, Prasramsini can be most suitably correlated with 1st and 2nd degree uterine prolapse. The management principle of pelvic organ prolapse includes Vathika yoniroga chikitsa along with Sthanika chikitsa. Treatment mainly aims at Vathasamana, Brimhana, Sandhana, Balya and strengthening of pelvic floor musculature. Sthanika chikitsa like Yonilepana, Yonipurana, Pichu dharana, etc can be done in pelvic organ prolapse. In Sthanika chikitsa, medicines are applied intravaginally. Vaginal wall and adjacent tissues are extremely vascular and this facilitates absorption of drugs through vagina. Anatomically backward position of vagina helps in self retaining of drugs for a longer duration. In the present case, Yonilepa as Sthanika chikitsa was tried. A 56 year old lady was presented with complaints of urinary incontinence, low back ache, dyspareunia and feeling of mass per vaginum. On examination, she was diagnosed with 1st degree uterine descend. USG was done to exclude other pelvic pathologies. Pap smear was done which was – ve for intraepithelial lesion or malignancy. Lodhradi lepa was applied for 7 days in 3 consecutive months. During follow up, she was relieved from symptoms like feeling of mass per vaginum, urinary incontinence, low back ache and dyspareunia. From this case report, it is evident that Yoni lepa is effective for the management of uterine prolapse.